SUFIKS â€“ING DALAM JURNAL â€œENGLISH TEACHING FORUMâ€ VOLUME 45 - LAMUNDE, UCI SUFRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This skripsi entitled suffix â€“ing in journal â€œEnglish Teaching Forumâ€ : a Â Syntactical Analysis. The -Ing form is neutral with respect to time; the time that is intended often depends on the tense or the meaning of the main verb. The suffix -ing is often used loosely instead of the perfect form of the gerund object of verbs. The suffix -ing of a verb can be used as a present participle, Frank (1972: 315). This research aims at identifying, classifying, and analyzing, the suffix -ing used in journal â€œEnglish Teaching Forumâ€ in terms of forms and functions. The data of the suffix -ing were collected from journal article chapter 1-5 based on Arts and Artsâ€™s (1982: 167), Ladoâ€™s (2008: 24-62), Quirk. et alâ€™s., (1972: 242: 246) and Phillipsâ€™s (2000: 117)â€™s theories. In analyzing the data in terms of forms and function, the concept of Arts and Arts (1982: 167), were used. The method of this research is descriptive qualitative method. The results of this research show that the suffix -ing used in the sentences of the journal â€œEnglish Teaching Forum are various namely : suffix -ing as present continuous tense (3 data), past continuous tense (1data), gerund (9 data), reduced clause (6 data), -ing form as adjective (25 data) and -ing form as clauses that have an explicit subject and non explicit subject (21 data ). Furthermore the -ing forms have three functions: as verb, noun and as adjective. The study results show that the â€“Ing form functioning as adjective is the most used in the journal articles mentioned. Â  Key Words: The suffix -ing, Journal : English Teaching Forum